The Moral Organization Key Issues, Analyses, and Solutions - Ellemers, Naomi; de Gilder, Dick. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Investors, customers and employees increasingly expect organizations to take responsibility for the social impact of their activities. This book applies theory and research on moral psychology and social identity, to offer a new perspective on organizational social responsibility and business ethics. The authors use their unique approach to highlight recurring moral challenges in organizational behavior, such as leadership, work motivation, diversity, organizational change and stakeholder relations. Their analysis explains that people are reluctant to acknowledge and confront moral flaws in their workplace behavior, because this constitutes a source of identity threat. Common strategies to cope with this threat invite justifications and symbolic actions - and prevent moral improvement. Each chapter draws together a wealth of research findings and organizational cases. These not only identify and clarify common moral pitfalls, but also show ways to enhance the likelihood that organizations acquire the knowledge, willingness and ability to build an ethical work climate. It seems that a week doesn't go by without a new headline about an organizational scandal. With "The Moral Organization," Ellemers and de Gilder have done an enormous service for us all by using a social identity lens to demystify why it's often so hard to do the right thing in organizational life and how organizational members, groups, and institutions themselves can be encouraged to change. This is a deeply researched, immensely accessible book written by two expert guides on an always-timely topic. Blake Ashforth, PhD. Regents Professor and Horace Steele Arizona Heritage Chair, W.P. Carey School of Business, Arizona State University, United States of America There are three key types of scholarly text: those that describe the world, those that explain the world, and those that change the world. This book does all three. In it, Ellemers and de Gilder not only do a superb job of charting the complex terrain of morality as it pertains to organizational life, but they also bring a fresh and vital perspective to the topic that allows readers to appreciate and master the complex challenges of becoming - and remaining - a moral organization. Deeply illuminating but also immensely empowering, this is a monumental text that will stand as a lighthouse for the field for decades ahead. Alex Haslam, PhD. Professor of Social and Organizational Psychology and Laureate Fellow, University of Queensland, Australia.
Chapter 1: Moral behavior in organizations -- Chapter 2: Social identity at work -- Chapter 3: Moral leadership -- Chapter 4: Motivating moral choices -- Chapter 5: Diversity and inclusion -- Chapter 6: The human factor in organizational change -- Chapter 7: Relating to stakeholders -- Chapter 8: The power of ethical climates. .
Keywords: Personality; Difference (Psychology).; Psychology, Industrial; Business ethics; Personality and Differential Psychology; Work and Organizational Psychology; Business Ethics; Business Ethics